2014
DOI: 10.3389/fncir.2014.00011
|View full text |Cite
|
Sign up to set email alerts
|

Information-geometric measures estimate neural interactions during oscillatory brain states

Abstract: The characterization of functional network structures among multiple neurons is essential to understanding neural information processing. Information geometry (IG), a theory developed for investigating a space of probability distributions has recently been applied to spike-train analysis and has provided robust estimations of neural interactions. Although neural firing in the equilibrium state is often assumed in these studies, in reality, neural activity is non-stationary. The brain exhibits various oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
(112 reference statements)
0
3
0
1
Order By: Relevance
“…In another fish species, several visual features, such as shoal size [ 22 25 ], sex [ 24 , 25 ], familiarity [ 22 ], body colouration [ 26 , 27 ], and body size [ 22 , 28 , 29 ], affect the formation of fish shoals. Although previous studies have primarily focused on what role morphological features of visual cues have in the social approach behaviour, perception of visual motion is one of the most basic abilities of fish as well as other vertebrates [ 30 , 31 ]. We recently showed that visual motion cues play critical roles in the decision making of medaka in studies on hunting behaviour against the modelled motion of zooplanktons [ 32 ] and social approach behaviour induced by biological motion stimuli of conspecific fish [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another fish species, several visual features, such as shoal size [ 22 25 ], sex [ 24 , 25 ], familiarity [ 22 ], body colouration [ 26 , 27 ], and body size [ 22 , 28 , 29 ], affect the formation of fish shoals. Although previous studies have primarily focused on what role morphological features of visual cues have in the social approach behaviour, perception of visual motion is one of the most basic abilities of fish as well as other vertebrates [ 30 , 31 ]. We recently showed that visual motion cues play critical roles in the decision making of medaka in studies on hunting behaviour against the modelled motion of zooplanktons [ 32 ] and social approach behaviour induced by biological motion stimuli of conspecific fish [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al ( 2014 ) make use of Information Geometry (IG), which is based on the expansion of the joint probability distribution of an N-neuron system. They used two measures, the single-IG measure and the pairwise IG-measure to examine the activity of simulated interconnected neurons that exhibit oscillations.…”
Section: Network Functionalitymentioning
confidence: 99%
“…The interrelation of the geometry and certain statistical models has been considered too (see e.g. [10][11][12][13][14]).…”
Section: Introductionmentioning
confidence: 99%